Analysis of the evaluation value of quantitative perfusion histogram parameters in DCE-MRI for extramural venous invasion in rectal cancer patients - Zhou Kunsheng; Guo Xin; Chen Fang; Peng Zebiao (结直肠肛门外科)
[Objectives] To analyze the evaluation value of quantitative perfusion histogram parameters in dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) for extramural venous invasion (EMVI) in rectal cancer patients. [Methods] A retrospective analysis was conducted on the clinical data of 96 patients who underwent laparoscopic low anterior resection for rectal cancer in our hospital from October 2020 to December 2022. Based on postoperative pathological results, patients were divided into the observation group (EMVI positive, n＝38) and the control group (EMVI negative, n＝58). Clinical data, DCE-MRI image data, and histogram parameters of all patients were collected to analyze the evaluation value of DCE-MRI quantitative perfusion histogram parameters for EMVI in patients with rectal cancer. [Results] The median, mean, and 90th percentile value of Ktrans, Kep, and Ve in the observation group were higher than those in the control group. Additionally, the 10th percentile value of Kep in the observation group was higher than that in the control group (P<0.05). The evaluation performance of Kep 10th percentile and Ve 90th percentile was poor (0.5<AUC≤0.7). However, the evaluation performance of Ktrans median, mean, and 90th percentile; Kep median, mean, and 90th percentile; Ve median and mean was good (0.7<AUC≤0.9), among which the evaluation performance of Kep median, mean, and 90th percentile was relatively better (AUC≥0.8). [Conclusion] The evaluation performance of DCE-MRI quantitative perfusion histogram parameters Kep median, mean, and 90th percentile for EMVI status in patients with rectal cancer is relatively good, which can provide a certain reference basis for preoperative evaluation of EMVI status and the development of treatment plans in rectal cancer.